2015
DOI: 10.1063/1.4929829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rapid thermal annealing on barrier height and 1/f noise of Ni/GaN Schottky barrier diodes

Abstract: Current-voltage (as a function of temperature), capacitance-voltage, and 1/f noise characteristics of Ni/GaN Schottky barrier diodes (SBDs) as function of rapid thermal annealing (RTA) are studied. It is found that RTA treatments of SBDs at 450 degrees C for 60 s resulted in a significant improvement of ideality factor and Schottky barrier height: the ideality factor decreased from 1.79 to 1.12 and the barrier height increased from 0.94 to 1.13 eV. The spectral power density of current fluctuations in the diod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 42 publications
2
30
0
2
Order By: Relevance
“…Figure a shows the J–V characteristics of graphene/hBN/n‐GaN device with respect to temperature (298–373 K). Increase in forward current and reduction in turn‐on voltage were observed with the increase in temperature . Figure b shows the semi‐logarithmic plot for forward and reverse bias J – V characteristics.…”
Section: Resultsmentioning
confidence: 97%
“…Figure a shows the J–V characteristics of graphene/hBN/n‐GaN device with respect to temperature (298–373 K). Increase in forward current and reduction in turn‐on voltage were observed with the increase in temperature . Figure b shows the semi‐logarithmic plot for forward and reverse bias J – V characteristics.…”
Section: Resultsmentioning
confidence: 97%
“…These results are similar to those obtained for the GaN‐based Schottky contact. Kumar et al reported that the ideality factor is decreased from 1.10 at 80 K to 3.5 at 320 K , and the barrier height is increased from 0.3 eV at 80 K to 1.2 eV at 320 K for Ni/GaN Schottky structures.…”
Section: Resultsmentioning
confidence: 99%
“…More detailed explanation is give elsewhere. 27,28 From the I-V-T measurement results, it is believed that the effect of ideality factor greater than 1 for all temperatures can be modeled by considering current transport in the device to be explained by thermionic field-emission. The forward bias current transport mechanism is mostly determined by the value of the ideality factor.…”
Section: Resultsmentioning
confidence: 99%